Modern Latin: Vol. 1 - Sadler, Jefferson Davifrey50 (Norman, University of Oklahoma Press, 1973)
A text for teaching the student to read Latin using a small basic vocabulary, the principles of word building, and simplified grammar.
Keywords: Latin language -- Grammar; Latin language -- Grammar